(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The main objective of this study was to investigate the impact of Bancassurance model on the financial performance of selected commercial banks. For achieving the objectives data was collected from 10 public sector commercial bank. The selection of banks is based on simple random sampling. Under the study bank performance as dependent variables and Cost-to-income Ratio, Yield on Advances, Net Interest Margin, Cost of Deposits, Yield on Funds are designated as independent variable. The major outcome of the study is Yield on Advances, Cost of Deposits, Yield on Funds, Cost-to-income Ratio significantly improves Bank performance. Except, net Margin not have a significant impact on performance of bank.